2010
DOI: 10.1111/j.1834-7819.2010.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

The University of Newcastle’s first cohort of Bachelor of Oral Health students: a social profile

Abstract: Background: This paper reports on the socio-demographic characteristics of the first year cohort of 52 students enrolled in the Bachelor of Oral Health programme at the University of Newcastle, New South Wales. Methods: Forty students completed paper-based questionnaires. Results: Results show that the cohort is predominantly female (94%), the mean age of students was 26.3 years and 72.5% of students had worked as dental chairside assistants prior to enrolment as mature-entry students. Conclusions: This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
1
5
0
2
Order By: Relevance
“…It is interesting to note that a significant proportion of these students were previously employed as a dental assistant/auxiliary. These trends were also observed by Wallace and her collaborators amongst BOH students in Newcastle University. This finding might suggest that the applicants may not be aware of this course whilst in secondary school, but decided later to commence study after gaining information or coming into contact with the profession working in the dental team.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…It is interesting to note that a significant proportion of these students were previously employed as a dental assistant/auxiliary. These trends were also observed by Wallace and her collaborators amongst BOH students in Newcastle University. This finding might suggest that the applicants may not be aware of this course whilst in secondary school, but decided later to commence study after gaining information or coming into contact with the profession working in the dental team.…”
Section: Discussionsupporting
confidence: 66%
“…Recent studies have indicated that the profile of dental students studying at Australian and New Zealand universities is changing rapidly . Student profiles in these programmes have changed towards more diversity in their ethnic and cultural background . There is, however, limited data available on the sociodemographic profile and career decisions, of BOH students across Australia and New Zealand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El motivo de la elección del instrumento de evaluación MBI-SS fue realizado dentro de varios aspectos, por el hecho de haber sido elaborado y validado en diversos países para investigación de la SB en estudiantes, concordando con Galán et al (2011)22 , la comparación de nuestros resultados con otros estudios no es una tarea fácil, debido a la variedad de instrumentos utilizados, la poca utilización del instrumento escogido en las investigaciones con estudiantes de odontología y la definición de criterios para determinar la presencia del síndrome de burnout.Al contrario de cualquier dificultad, en los últimos años ha sido notoria la feminización de la profesión odontológica23,24 , lo que corrobora con nuestros resultados a nivel de pregrado. Esta transición puede ser percibida cuando observamos los datos de Gietzelt (1997)25 , los cuales señalan que 44.4% de los estudiantes en el primer año del curso de odontología en Sydney son del género femenino.…”
unclassified
“…Esta transición puede ser percibida cuando observamos los datos de Gietzelt (1997)25 , los cuales señalan que 44.4% de los estudiantes en el primer año del curso de odontología en Sydney son del género femenino. En un estudio realizado en Newcastle, New South Wales, también Australia, con estudiantes que iniciaron el curso en el año 2005, el resultado fue que 94% de los estudiantes ingresantes son del género femenino23 . En Brasil, en estudio realizado en Goiás, señala que 64.9% de los egresos entre 1988 y 2007 son mujeres24 .El estudio de Martínez et al (2008)26 , realizado con estudiantes de la Universidad de Barcelona, encontró que los hombres son más susceptibles al burnout que las mujeres y sugirió como una posible causa del hecho que las mujeres son más propensas a buscar ayuda de colegas y apoyo familiar.…”
unclassified